PENGARUH UPAH DAN TEKNOLOGI TERHADAP PRODUKTIVITAS DAN PENYERAPAN TENAGA KERJA PADA INDUSTRI MEBEL DI KOTA DENPASAR - Nashahta Ardhiaty Nurfiat; Surya Dewi Rustariyuni (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2018)
Small industry has a very important role in the Province of Bali, especially in the city of Denpasar in providingemployment opportunities for the community. The development of this small industry will reduce unemployment andpoverty. The purpose of this study is to analyze 1) The influence of wage and technology level on work productivity2) Effect of wage rate, technology and work productivity on labor absorption 3) Indirect influence of wage andtechnology level on labor absorption through work productivity. This research was conducted in Denpasar Citywith respondents of wooden furniture industry entrepreneurs covering 4 subdistricts namely North Denpasar, EastDenpasar, South Denpasar and West Denpasar. Objects in this study include wage rates, technology, work productivityand employment. The sample in this study amounted to 104 respondents. The sample technique used is probabilitysampling or simple random sampling. Data collection methods used in this study include observation, questionnairesand in-depth interviews. Data analysis technique used is path analysis / path analysis and test of sobel to analyzeindirect influence through intervening variable. Based on the research results obtained conclusion that the level ofwages and technology postive and significant influence on the productivity of wood furniture industry desk work.Variable wage rate, technology and work productivity have a positive and significant effect to the absorption oflabor of wooden table furniture industry in Denpasar City. Work productivity variable is the variable of mediationof indirect influence of variable of wage rate and technology to the absorption of labor in wooden furniture industryin Denpasar City. Suggestion from this research entrepreneurs have the policy of giving the right incentive or bonusto the workforce so as to increase the production.